Fluorescence of pterin, 6-formylpterin, 6-carboxypterin and folic acid in aqueous solution: pH effects - Thomas, Andrés Héctor (2002)
Steady-state and time-resolved studies have been performed on four compounds of the pterin family (pterin, 6-carboxypterin, 6-formylpterin and folic acid) in aqueous solution, using the single photon counting technique. The fluorescence characteristics (spectra, quantum yields, lifetimes) of these compounds and their dependence on the pH have been investigated. Most pterins can exist in two acid–base forms over the pH range between 3 and 13. Emission spectra and excitation spectra were obtained for both forms of each compound studied. Fluorescence quantum yields (ΦF) in acidic and basic media were measured. The ΦF of folic acid (<0.005 in both media) is very low compared to those of pterin (0.27 in basic media and 0.33 in acidic media), 6-carboxypterin (0.18 in basic media and 0.28 in acidic media) and 6-formylpterin (0.07 in basic media and 0.12 in acidic; media). The variation in integrated fluorescence intensity and fluorescence lifetimes (τF) was analysed as a function of pH. Dynamic quenching by OH⁻ was observed and the corresponding bimolecular rate constants for quenching of fluorescence (kq) were calculated. The reported values for kq; (M⁻¹ s⁻¹) are 3.6 × 10⁹, 1.9 × 10⁹ and 1.1 × 10¹⁰ M⁻¹ s⁻¹ for pterin, 6-carboxypterin and 6-formylpterin, respectively.